(untitled) (Palimpsesto, 2019)
This project presents evidence of an investigation based on a qualitative study, with an empirical phenomenological approach, focused on analyzing the perceptions of a group of adolescent mothers versus the communication link established with their babies in everyday situations, taking into account the lack of awareness, even among some professions, about the importance of establishing the link for early communication development. Three types of relationships were observed in the analyzed families , these were: communication, adult role and social affectivity ,each represented different codes and quotes that showed the perception and the establish of the link from the perspective of the adolescent mother.